Sleep hygiene education for improving sleep in ultra-marathon swimmers: Guidance for coaches and swimmers - Dunican, I. C.; Perry, E.; Maisey, G.; Nesci, E.; Roberts, S. (International Journal of Sports Science & Coaching, 2023)
Sleep for recovery is an essential factor for performance in athletes. One such group is recreational ultra-marathon swimmers (>10km). We aimed to compare measures of sleep before and after a sleep hygiene education intervention during a 16-week training programme. Using a prospective study design, the experiment was conducted in two phases (pre- and post-intervention), whereby pre- and post-intervention data were collected for 42 nights after the sleep hygiene education. This study had 24 masters` swimmers (n = 13 females), aged 39 ± 11 years, and body mass index (BMI) of 26 ± 3 kg/m2 during a training squad for an ocean ultra-marathon swimmer (19.7 km) in Perth, Western Australia. Objective measures of sleep were obtained from a wrist activity monitor, the Readiband™ (Fatigue Science Inc., Canada). Participants underwent a 2-hour sleep hygiene education session. Generalised linear mixed models were fitted to examine relationships between predictor variables and sleep responses. Sleep onset and offset increased by 12 minutes post-intervention (p < 0.001). For nights before morning training, sleep onset increased by 12 minutes and offset by 24 minutes post-intervention. Females increased sleep onset by 18 minutes and delayed sleep offset by 12 minutes sleep (p < 0.05) post-intervention. The sleep hygiene education was insufficient in making meaningful improvements to measures of sleep. Individual sleep hygiene education and continuous reinforcement of sleep for recovery during a training programme may be required to observe improvements. Coaches should aim to design training schedules to minimise the impact on swimmer`s sleep opportunity and swimmers need to involve family in the planning of rest periods during a training programme.